On Effective Locations of Catalytic Active Sites in Phase Boundary Catalysts - Hadi Nur; Nur Hidayah Mohd Ran; Nursyafreena Attan; Shigeru Ikeda; Bunsho Ohtani (Institute for Research and Community Services (LPPM) ITB, 2012)
Zeolite loaded with alkylsilane-covered titanium oxide was found to be more effective than its nonporous silica counterpart as phase-boundary catalyst (PBC) to promote epoxidation of alkenes with aqueous hydrogen peroxide. It was demonstrated that the phase-boundary catalyst system required neither stirring to make an emulsion, nor addition of a cosolvent to make a homogeneous solution to drive the reaction. However, some basic facts about them remain unclear, such as the question as to where an effective location of the active sites of PBC resides: is it on the external surface of the catalysts, or in their pores? In order to elucidate this problem, TS-1, HZSM-5 and zeolite loaded with alkylsilane